miR-4516 predicts poor prognosis and functions as a novel oncogene via targeting PTPN14 in human glioblastoma - Cui, Tiantian (Oncogene, 2018)
Glioblastomas (GBMs) are the most aggressive primary brain tumors, with an average survival of less than 15 months. Therefore, there is a critical need to develop novel therapeutic strategies for GBM. This study aimed to assess the prognostic value of miR-4516 and investigate its oncogenic functions and the underlying cellular and molecular mechanisms in GBM. To determine the correlation between miR-4516 expression and overall survival of patients with GBM, total RNAs were isolated from 268 FFPE tumor samples, miR expression was assayed (simultaneously) using the nCounter human miRNA v3a assay followed by univariable and multivariable survival analyses. Further, in vitro and in vivo studies were conducted to define the role of miR-4516 in GBM tumorigenesis and the underlying molecular mechanisms. Upon multivariable analysis, miR-4516 was correlated with poor prognosis in GBM patients (HR=1.49, 95%CI: 1.12–1.99, p=0.01). Interestingly, the significance of miR-4516 was retained including MGMT methylation status. Overexpression of miR-4516 significantly enhanced cell proliferation and invasion of GBM cells both in vitro and in vivo. While conducting downstream targeting studies, we found that the tumor-promoting function of miR-4516, in part, was mediated by direct targeting of PTPN14 (protein tyrosine phosphatase, non-receptor type 14) which, in turn, regulated the Hippo pathway in GBM. Taken together, our data suggest that miR-4516 represents an independent negative prognostic factor in GBM patients and acts as a novel oncogene in GBM, which regulates the PTPN14/Hippo pathway. Thus, this newly identified miR-4516 may serve as a new potential therapeutic target for GBM treatment.